Uma abordagem orientada a objetivos para desenvolvimento de ontologias baseado em integração - Salamon, Jordana Sarmenghi (2018)
Reuse has been pointed out as a promising approach for Ontology Engineering. Reuse allows speeding up the development process and improving the quality of the resulting ontologies, since it promotes the application of good practices. In the Ontology Engineering context, one of the forms of reuse involves the integration of existing ontologies. Ontology integration can be defined as the integration of source ontologies into an integrated ontology, to which concepts and relations beyond those found in the source ontologies can be added. Integration depends on finding ontologies that satisfy the requirements of the ontology being developed. However, often, the available ontologies do not explicit their design rationale, which makes it difficult to understand the source ontologies and, consequently, integrate them. Making explicit the design rationale of the ontology developed from integration is also important to assist in the search for source ontologies that meet the requirements of the integrated ontology. Although there are ontology development approaches that recognize the importance of integration in this context, and also approaches that deal specifically with the integration process, there is a lack of approaches that guide the ontology engineer in an integration-based ontology development process and that are concerned with the rationale of the ontology being developed. Goal modeling has been pointed out as a way to support ontology requirements elicitation. In this sense, the ability of goal models to represent motivational aspects of ontology development can be explored to make explicit the design rationale behind an ontology. Thus, this work proposes Integra, a goal-oriented approach for ontology development based on integration. In order to evaluate Integra, it was used in a proof of concept and in a case study.